2007
DOI: 10.1590/s0100-879x2007000200006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an aerobic training program on the electrical remodeling of the heart: high-frequency components of the signal-averaged electrocardiogram are predictors of the maximal aerobic power

Abstract: Increased heart rate variability (HRV) and high-frequency content of the terminal region of the ventricular activation of signal-averaged ECG (SAECG) have been reported in athletes. The present study investigates HRV and SAECG parameters as predictors of maximal aerobic power (VO 2 max) in athletes. HRV, SAECG and VO 2 max were determined in 18 high-performance long-distance (25 ± 6 years; 17 males) runners 24 h after a training session. Clinical visits, ECG and VO 2 max determination were scheduled for all at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The differences in genders and ages are well established in the literature, women show slightly lower HRV values and higher parasympathetic activity . Nevertheless, as observed in three studies included in this review, the use of heterogeneous groups as part of the same sample did not appear to influence the results.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The differences in genders and ages are well established in the literature, women show slightly lower HRV values and higher parasympathetic activity . Nevertheless, as observed in three studies included in this review, the use of heterogeneous groups as part of the same sample did not appear to influence the results.…”
Section: Discussionsupporting
confidence: 53%
“…The total number of athletes was about 333 males and females, aged between 17 and 40 years, who practiced different sports (running, cycling, swimming, canoeing, athletics, skating, volleyball, football, basketball, rugby, and triathlon). For the sample characterization, seven studies used the VO 2 as a physiological measure, seven studies reported the length of time that the athletes had practiced the sport (over 2 years), and eight studies selected athletes participating in national, regional, or international competitions . No study reported the athlete's training phase during the course of the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations